2016
DOI: 10.1088/0741-3335/58/2/025008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic simulations of the Chodura and Debye sheaths for magnetic fields with grazing incidence

Abstract: When an unmagnetized plasma comes in contact with a material surface, the difference in mobility between the electrons and the ions creates a non-neutral layer known as the Debye sheath (DS).However, in magnetic fusion devices, the open magnetic field lines intersect the structural elements of the device with near grazing incidence angles. The magnetic field tends to align the particle flow along its own field lines, thus counteracting the mechanism that leads to the formation of the DS.Recent work using a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 22 publications
5
48
1
Order By: Relevance
“…in the numerator of k 3/2 is equal to zero, which means that k 3/2 = 0 and the correct form of the potential at x → ∞ is given by equation (112). The value of k 2 in the cold ion limit, k 2,cold , is obtained from (111) At sufficiently large x, C 2,cold can be neglected and Chodura's result for the scaling of the potential at the magnetic presheath entrance x → ∞ is recovered (this scaling is obtained from Chodura's paper [10] by combining equations (22), (23), and the equation immediately after (24), and noting that Chodura's notation is ψ = π/2 − α and his derivation is valid for general ψ).…”
Section: Appendix A2 Gyrophase Expansionmentioning
confidence: 99%
“…in the numerator of k 3/2 is equal to zero, which means that k 3/2 = 0 and the correct form of the potential at x → ∞ is given by equation (112). The value of k 2 in the cold ion limit, k 2,cold , is obtained from (111) At sufficiently large x, C 2,cold can be neglected and Chodura's result for the scaling of the potential at the magnetic presheath entrance x → ∞ is recovered (this scaling is obtained from Chodura's paper [10] by combining equations (22), (23), and the equation immediately after (24), and noting that Chodura's notation is ψ = π/2 − α and his derivation is valid for general ψ).…”
Section: Appendix A2 Gyrophase Expansionmentioning
confidence: 99%
“…Close to the wall in the magnetic presheath, the time it takes for an ion to intersect the wall is a typical ion gyroperiod, while the time it takes for an electron (due to its much smaller Larmor radius) is given by its faster streaming along the field line towards the wall, as shown in Figure 3. The criterion that must be satisfied for electrons to reach the wall faster, leading to a negatively charged wall, is α m e /m i 0.02 ( 1 • ) [31,35], where m e and m i are the electron and ion mass respectively, and the estimate is made using the mass of a deuterium ion. Hence, we assume m e m i α 1.…”
Section: Orderingsmentioning
confidence: 99%
“…Note that if we takeĒ and E both positive and only look at the region where both x and dφ/dx are positive, the electric field is directed towards x = 0 (the wall) and increasing as x gets smaller, which is qualitatively similar to the electric field in the magnetic presheath. In this section, we use equations (26), (27), (30), (31) and (33), which are valid for a general electric field, in order to solve the zeroth order problem with the linear electric field (E.1). The effective potential in the linear electric field is…”
Section: Appendix E the Zeroth Order Problem With A Linear Electric mentioning
confidence: 99%
“…Instead of using the PIC method, our code employs a continuum kinetic method for its inherent lack of statistical noise and good resolution of distribution functions. These advantages are particularly valuable for studies involving sheaths, as shown by other recent works [46,47,48]. Here, the number of particles per unit phase space volume fs(x,vs,t) for each charge species s is calculated by advancing the kinetic Boltzmann Transport Equation explicitly over a uniform finite difference 1D-1V grid where the velocity direction is normal to the electrodes (vs = vs,x in this section).…”
Section: A Continuum Kinetic Codementioning
confidence: 99%